Citizen science project (CSP) learning model as innovation learning in improving 21st century skills - Adnan Adnan; Sitti Saenab; Rahmatullah Rahmatullah; Rifka Almunawarah; Sahla Sahira; Maghfirah Alma Aulia; Hikmah Nurul Jannah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Learning models that are in line with the challenges of the 21st century, namely involving students to think critically, creatively, and be able to communicate and collaborate are very important to develop. One of the learning models that support this is the Citizen Science Project (CSP) model. This research uses the development method with the ADDIE approach, which consists of the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The CSP learning model consists of syntax, reaction principles, social systems, support systems, and instructional and accompanying impacts. The focus of this research is up to the implementation stage, which involves analysing the validation of the CSP model as well as the practicality test by teachers and learners. The instruments used in the study included a validation questionnaire for two expert validators, as well as a practicality questionnaire for 2 teachers and 34 learners. The data were analysed based on the feasibility of the CSP model, as assessed by the validators, as well as practicality from the perspective of teachers and learners. The validation results showed an average score of 4.38 out of 5, which falls into the valid category. Practicality assessment by learners resulted in a score of 83.2 which is included in the very practical category, while teachers gave a score of 84.8 which is also included in the very valid category. Based on these results, it can be concluded that the CSP learning model is valid and very practical to be applied to support 21st century learning in improving 4C skills.Abstrak. Model pembelajaran yang selaras dengan tantangan abad ke-21, yaitu melibatkan siswa untuk berpikir kritis, kreatif, serta mampu berkomunikasi dan berkolaborasi, sangat penting untuk dikembangkan. Salah satu model pembelajaran yang mendukung hal ini adalah model Citizen Science Project (CSP). Penelitian ini menggunakan metode pengembangan dengan pendekatan ADDIE, yang terdiri dari tahap analisis, tahap desain, tahap pengembangan, tahap implementasi, dan tahap evaluasi. Model pembelajaran CSP terdiri atas sintaks, prinsip reaksi, sistem sosial, sistem pendukung, serta dampak instruksional dan dampak penyerta. Fokus penelitian ini hingga tahap implementasi, yang melibatkan analisis validasi model CSP serta uji kepraktisan oleh guru dan peserta didik. Instrumen yang digunakan dalam penelitian ini mencakup kuesioner validasi untuk dua validator ahli, serta kuesioner kepraktisan untuk dua guru dan 34 peserta didik. Data dianalisis berdasarkan kelayakan model CSP yang dinilai oleh validator, serta kepraktisannya dari perspektif guru dan peserta didik. Hasil validasi menunjukkan skor rata-rata 4,38 dari 5, yang termasuk dalam kategori valid. Penilaian kepraktisan oleh peserta didik menghasilkan skor 83,2, yang termasuk dalam kategori sangat praktis, sedangkan guru memberikan skor 84,8, yang juga termasuk dalam kategori sangat valid. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model pembelajaran CSP valid dan sangat praktis untuk diterapkan guna mendukung pembelajaran abad ke-21 dalam meningkatkan keterampilan 4C.